Empowering Health Cadres as Stunting Center Managers - Elly Dwi Masita; Pratiwi Hariyani Putri; Heni Agustina; Evi Tasya Azahro; Rizkiyah; Jessica Puspa Kencana; Nur Maulidyah Azizah (Community Development Journal, 2023)
At present, stunting in children aged 3-5 years is the biggest child health problem experienced by most developing countries including Indonesia. A survey conducted in January 2023 with local health officials found that out of 170 toddlers, 30 were malnourished in the form of underweight, 18 toddlers and 12 toddlers were indicated to be stunted with parents who had low economic status. The general objective of this activity is focused on achieving health independence through establishing information centres and stunting management facilities managed by health cadres as an effort to prevent an increase in stunting prevalence as well as a facility to increase the income of families who have children at risk of nutritional problems, families who are indicated to be stunted through stunting centres. The activity method uses an assessment-based community development approach through seminars, training and mentoring. The instrument uses questionnaires and checklists. Indicators of achievement are the level of knowledge, skill level and income of families with infants and toddlers at risk of malnutrition and stunting. The target partners are 55 health cadres and 55 mothers who have babies and toddlers aged 5 years in the Sidoarjo area. The results of this activity found that there was a difference in the mean in each indicator of achievement of the level of knowledge of 66.6. Food management skills of 66.2, health-based entrepreneurship skills of 64.3 and family income indicators of 1.63 and Whitney mean test results with Sig = 0.001. The community development-based assessment approach method through seminars, training and mentoring is effective in changing the level of knowledge, perception and behaviour of health cadres and mothers who have infants and toddlers in fulfilling nutrition and improving the family economy as a form of support for stunting reduction programs, family food security as well as family economic security